2000
DOI: 10.1034/j.1399-0039.2000.550301.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA haplotypes are associated with differential susceptibility to Trypanosoma cruzi infection

Abstract: We explored a possible role of HLA class II genes in determining the susceptibility to Trypanosoma cruzi infection as well as in the development of chagasic heart disease in a rural mestizo population from Arequipa (Southern Peru). HLA-DRB1 and DQB1 polymorphisms were determined in 85 seropositive (asymptomatic, n=52; cardiomyopathic, n=33) and 87 seronegative individuals. We observed that the DRB1*14-DQB1*0301 haplotype correlates with not having T. cruzi infection in a highly endemic area (OR= 0.26 (0.124.63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 18 publications
3
28
0
1
Order By: Relevance
“…Another study on this population in an endemic region revealed an association of the HLA-DRB1*01-DQB1*0501 haplotype with cardiomyopathy [71]. The HLA-DRB1*01-DQB1*0501-DPB1*0401 haplotype is mentioned by Fernández-Mestre et al (2002) as a marker of susceptibility to Chagas' disease in Venezuela [72], while HLA-DRB1*14-DQB1*0301 was associated with noninfection by T. cruzi in individuals inhabiting a highly endemic area in Peru [73]. Overtvelt et al (2002) demonstrated that HLA class I also participates in the escape mechanism of T. cruzi from the immune response, associating greater expression of some of these molecules with longer persistence of the parasite in the host organism without eliciting an immune response [74].…”
Section: Parasitic Infectionsmentioning
confidence: 91%
“…Another study on this population in an endemic region revealed an association of the HLA-DRB1*01-DQB1*0501 haplotype with cardiomyopathy [71]. The HLA-DRB1*01-DQB1*0501-DPB1*0401 haplotype is mentioned by Fernández-Mestre et al (2002) as a marker of susceptibility to Chagas' disease in Venezuela [72], while HLA-DRB1*14-DQB1*0301 was associated with noninfection by T. cruzi in individuals inhabiting a highly endemic area in Peru [73]. Overtvelt et al (2002) demonstrated that HLA class I also participates in the escape mechanism of T. cruzi from the immune response, associating greater expression of some of these molecules with longer persistence of the parasite in the host organism without eliciting an immune response [74].…”
Section: Parasitic Infectionsmentioning
confidence: 91%
“…These two antigens are the most frequent reported in several healthy American populations, including the Mexicans (both Mestizos and Amerindians) [19 -21]. A study in a rural mestizo population from Peru reported a protective effect of the HLA-DR14 DQB1*0301 haplotype in the T. cruzi infection; however, they did not detect association with chagasic heart disease [14]. Other reports suggest associations of cardiac damage with both class I and class II alleles, but the results have been heterogeneous [13].…”
Section: Mhc Class I (Hla-a and -B) And Class Ii (Hla-dr)mentioning
confidence: 99%
“…Murine models revealed that cytotoxic lymphocytes CD8 ϩ T cells are essential to eliminate parasites, and autoimmune mechanisms have been reported to play an important role in the development of chronic Chagas heart disease, both in experimental models and in humans [10,11]. Previous studies have suggested participation of major histocompatibility complex (MHC) genes on the susceptibility or resistance to T. cruzi infection and on the development of cardiac disease [12][13][14][15][16]. Thus, the aim of the present study was to investigate the possible role of MHC genes in determining the susceptibility to Trypanosoma cruzi infection as well as in the development of chagasic heart disease in the Mexican mestizo population.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the expression of genes related to the immune response may be involved. In humans there are studies addressing the relation between the major histocompatibility complex genes and CD (Nieto et al 2000). In addition, the C3F allele has been proposed as a marker for the progression of cardiomyopathy (Messias-Reason et al 2003).…”
mentioning
confidence: 99%